Systemy społeczno-gospodarcze nowych krajów przemysłowych Azji Wschodniej w globalnej gospodarce - Drelich-Skulska, Bogusława (Socio-Economic Systems of New Industrial Countries of Eastern Asia in Global Economy, 2008)
Socio-economic systems of New Industrial Countries (NICs) in East Asia were shaped in the second half of the 1960s under the influence of observation and adaptation of Japanese solutions. In the creation of development processes of NICs, leading economic and political role of the state, combined with an aversion to the West, were major functions. Since the middle of the 1980s major NICs economies led by South Korea, Taiwan, Singapore and Hong Kong opened up to the world, became export-oriented, active in acquiring modern technologies and foreign direct investment as their economic development philosophy, with strong support for free market. This development model was an answer to the dynamic integration of South-Eastern Asian economies with the global market. After the regional financial crisis which happened in 1997, a revision of this model became necessary. The currently created socio-economic systems of NICs in East Asia need deep structural reforms, strengthening of their financial systems, coordination of economic policy and development of pro-social policy which would promote quality social development. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 71-87